2019
DOI: 10.1016/j.scitotenv.2019.01.101
|View full text |Cite
|
Sign up to set email alerts
|

Belowground biota responses to maize biochar addition to the soil of a Mediterranean vineyard

Abstract: Biochar is a high carbon material resulting from biomass pyrolysis that, when applied to croplands, can increase soil carbon and soil water retention. Both effects are of critical importance in semi-arid regions, where carbon decline and desertification are the main drivers of soil degradation. Since most environmental services provided by soil are mediated by belowground biota, effects of biochar on soil microbial and invertebrate communities must be evaluated under field conditions before its agricultural ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 105 publications
0
12
0
3
Order By: Relevance
“…It typically possess a stable fixed carbon structure with high porosity, a high specific surface area and a high alkalinity. These characteristics enable biochar to enhance soil moisture content, sorb polluting substances and increase soil pH (Andrés et al, 2019). Moreover, biochar is considered carbon negative because the carbon within its structure, which is captured from the atmosphere during biomass formation, is more recalcitrant in the natural environment than carbon in biomass that has not been pyrolized.…”
Section: Biochar As a Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…It typically possess a stable fixed carbon structure with high porosity, a high specific surface area and a high alkalinity. These characteristics enable biochar to enhance soil moisture content, sorb polluting substances and increase soil pH (Andrés et al, 2019). Moreover, biochar is considered carbon negative because the carbon within its structure, which is captured from the atmosphere during biomass formation, is more recalcitrant in the natural environment than carbon in biomass that has not been pyrolized.…”
Section: Biochar As a Mitigationmentioning
confidence: 99%
“…Certain soil amendments are associated with increased soil biodiversity. For example, biochar amendment of a Mediterranean vineyard soil decreased the mineralization of both SOC and microbial biomass, while the functional microbial diversity and biodiversity of soil micro-arthropods were maintained (Andrés et al, 2019). Soil properties and biodiversity are also affected by plant root systems within the rhizosphere (Dey et al, 2012).…”
Section: Soil Biodiversitymentioning
confidence: 99%
“…Esta morfologia em folhas já é bem conhecida destes materiais obtidos de reagentes comerciais (Figueira et. al, 2008;Zhang et al, 2014;CUI et al, 2009 O biocarvão produzido a partir de resíduos de culturas agrícolas vem sendo utilizado em larga escala para melhoria da qualidade física e química dos solos (LEHMANN et al, 2011) e diversos estudos tem avaliado as contribuições deste material para biota edáfi ca (CHINTALA et al, 2016;ANDRÉS et al, 2019;HARDY et al, 2019;HERRMANN et al, 2019;PALANSOORIYA et al, 2019).…”
Section: Materiais E Métodounclassified
“…reported with Malus pumila woodchip BC (500°C), Eucalyptus saligna hardwood BC (550°C), and sugar maple wood BC (400°C) soil amendment, respectively. Additional studies found only modest or no differences[136,155,164,165]. The change in the composition of bacterial communities after incorporation of BC in soil is highly dependent on the preexisting bacterial community, soil type, and overall BC characteristics.Generally, the gram-negative bacterial community are favored in the nutrient-enriched BCamended soils and initially predominate the soil environment since they perform specific and narrow functions.…”
mentioning
confidence: 94%